Of social machines and human gears. Prison, the abject and the perverse in «El sexto» by José María Arguedas (Castilla. Estudios de Literatura, 2020)
This article studies El sexto (1961) of José María Arguedas. Our goal is to demonstrate that the author of this work intends to show that capitalism uses jail and inmates locked in this place to submit, control and punish those who dare to oppose their influence in Peru. In this sense, it is not just a prison novel, in which a particular harrowing experience is evoked, but a political text that highlights some of the strategies, instruments and mechanisms that are used to bend the will of insurgent individuals to that system.
Keywords: José María Arguedas; El sexto; prison novel; capitalism; perversion